Um estudo teórico e experimental da produção bioquímica de biodiesel de babaçu (Orbignya sp.) - Alexandre, Jeferson Yves Nunes Holanda (2022)
A theoretical and experimental study of the biocatalytic production of babassu biodiesel through enzymatic hydroesterification was carried out. Hydroesterification is a synthetic route based on hydrolysis followed by esterification. Complete hydrolysis of babassu oil was conducted using a 1:1 solution by weight at 40 °C for 4 hours using 0.4% lipase from Thermomyces lanuginosus (TLL) in relation to oil weight. Then, using Eversa® Transform 2.0 lipase in the esterification step, a statistical planning was carried out varying the parameters: temperature (25-55 °C), molar ratio free fatty acids (FFAs) and alcohol (1:1 to 1: 9), percentage of biocatalyst (0.1% to 0.9%) and reaction time (1-5 hours) using the Taguchi method. The percentage of biocatalyst was the most influential factor in the process with a contribution percentage equal to 67.80%. The ideal reaction levels obtained after statistical treatment were: L3 (5 hours) for time, L2 (40 °C) for temperature, L2 (1:5 AGL/alcohol) for molar ratio and L3 (0.9 % of mass in relation to the mass of FFA) for the percentage of biocatalyst, under these conditions, the theoretical conversion was 98.64%. After carrying out the proposed reaction, a conversion of 95.15% ± 0.1 was noted. The result of the optimized reaction was lower than the proposed theoretical conversion value, since biocatalysts can easily lose their catalytic activity, since these materials are susceptible to various interferences. The kinematic viscosity and density results indicate that the biodiesel produced has potential for future applications. Finally, a study of docking and molecular dynamics was carried out to evaluate the stability of the complexes formed between octanoic, decanoic, dodecanoic, tetradecanoic, hexadecanoic, and cis-9-octadecenoic acids and Eversa lipase. The protein was modeled by homology, through the Ramachandran diagram it was possible to identify the regions that maintained the conserved structure and the variable sites with alignment. In addition, the obtained model presented an average 3D-1D score ≥ 0.2 of 93.71% in the Verify 3D function, proving the compatibility of the atomic model with the amino acid sequence. It was observed in the molecular docking results that the ligands interacted directly with the catalytic site (Ser153, Asp206, and His268) and the oxyanion cavity (Leu154 and Ser91), these results suggest that the combinations between the ligands and the enzyme were stable. In the molecular dynamics simulations, it was verified through the Root Mean Square Deviation (RMSD) that there were no major conformational changes in the complexes studied during the simulation periods, with RMSD below 2.0 Å. Furthermore, the theoretical and experimental results presented in this work indicate that the fatty acids from babassu oil form stable complexes with the catalytic site of Eversa, which validates its application in the production of babassu methyl esters.